The influence of jazz and the reconstruction of the imagination in Sam Shepard’s Suicide in B-Flat: creating “a new dimension” in form and perception - Fernández-caparrós Turina, Ana (Estudios Ingleses de la Universidad Complutense, 2009)
The influence of music in the work of American playwright Sam Shepard has often been acknowledged but seldom granted the necessary critical attention, except for the highly original use of rock in The Tooth of Crime (1972). This article explores the experimentation inspired by jazz music in Suicide in B-Flat (1976). The freedom granted by jazz improvisation is connected in the play with the liberty of imagination and translated into a playful and decentered stage event. This sense of freedom with which jazz musicians rework previous material seem to have acted as the catalyst for an equal procedure in the dramatic realm, an exhortation to imaginatively search and conceive “new possibilities”, both in structural and conceptual terms. The use of jazz as a source of inspiration and as a principle of composition goes much further then than merely having musicians actually improvising on stage; the article explores how certain rhythmic experiments could be translated into devices for the alteration of dramatic structure or how the character’s discourse on jazz improvisation was used as metonymy for creation.